THE PHYSIOLOGICAL NEEDS’ FULFILLMENT OF STREET CHILDREN - Kurnajati, Sandy; Pramesti, Denok (Jurnal Penelitian STIKES Kediri, 2012)
Street children is a general term refers to children who have economical activity or life on the street. They still have a relationship with their family even though the families are far away from them. Some factors such as: economical status, educational status, and responsibility for making money cause lack of physiological needs’ fulfillment of street children. The purpose of this research was to study the physiological needs’ fulfillment of street children aged 6-12 years old according to Maslow Hierarchy on Kediri The design of this research was descriptive. This population was street children in Kediri. Using Quota Sampling, it was obtained 30 street children. The data were collected using questionnaires and interviews. The results showed 33.3% of the respondents had lack fulfillment on oxygenation and nutrition. Further, the majority of the respondents or 83.3% had play activities. Moreover, 13.3% of respondents had lack fulfillment on sleep rest pattern. In conclusion, study of street children aged 6-12 years old on Kediri showed that only play activities was properly fulfilled. The study described that 33.3% of the respondents had lack fulfillment on oxygenation and nutrition, 13.3% of respondents had lack fulfillment on sleep rest pattern.